Análisis de Materias Primas para la elaboración de Platos Biodegradables. (2021)
Disposable plastics are petroleum-based products; these are one of the products that generate the most pollution in both aquatic systems and terrestrial ecosystems, because many times people acquire them, use them and discard them without taking into account the long useful life that each one has, that is, they do not give them a second useful life, which generates large accumulations of them. Plastics decompose into materials of less than 5 millimeters known as microplastics, which affect the life of aquatic animals and people's health. In order to reduce the pollution generated by these products, 15 different raw materials for the production of biodegradable dishes are presented, which are: banana peel, banana leaves, coffee husk, coconut fiber, banana peel, achira leaves, Polylactic Acid (PLA), PLA and banana fiber mixture, PLA, banana fiber and silicate mixture, polyethylene, starch and synthetic resin mixture, wine bottle corks, PLA and starch mixture, pineapple crown and wheat flour. These plates degrade between 1 to 150 days depending on the raw material to be implemented, thus information was collected on the formation processes, time and percentage of degradation, as well as the physical-chemical characterization of each raw material. Finally, a matrix was prepared to determine which of the raw materials addressed are the best alternatives for the production of biodegradable plastics.